Uremic myopathy: is oxidative stress implicated in muscle dysfunction in uremia? - Kaltsatou, Antonia; Sakkas, Giorgos K.; Poulianiti, Konstantina P.; Koutedakis, Yiannis; Tepetes, Konstantinos; Christodoulidis, Grigorios; Stefanidis, Ioannis; Karatzaferi, Christina (Frontiers in Physiology, 2015)
Renal failure is accompanied by progressive muscle weakness and premature fatigue, in part linked to hypokinesis and in part to uremic toxicity. These changes are associated with various detrimental biochemical and morphological alterations. All of these pathological parameters are collectively termed ureamic myopathy. Various interventions while helpful can’t fully remedy the pathological phenotype. Complex mechanisms that stimulate muscle dysfunction in uremia have been proposed, and oxidative stress could be implicated. Skeletal muscles continuously produce reactive oxygen species (ROS) and reactive nitrogen species (RNS) at rest and more so during contraction. The aim of this mini review is to provide an update on recent advances in our understanding of how ROS and RNS generation might contribute to muscle dysfunction in uremia. Thus a systematic review was conducted searching PubMed and Scopus by using the Cochrane and PRISMA guidelines. While few studies met our criteria their findings are discussed making reference to other available literature data. Oxidative stress can direct muscle cells into a catabolic state and chronic exposure to it leads to wasting. Moreover, redox disturbances can significantly affect force production per se. We conclude that oxidative stress can be in part responsible for some aspects of uremic myopathy. Further research is needed to discern clear mechanisms and to help efforts to counteract muscle weakness and exercise intolerance in uremic patients.